Nurcholish Madjid’s Idea of Inclusive Theology in Islam - Munir A. Muin (UIN Sunan Gunung Djati Bandung, 2014)
Nurcholish Madjid was one of Indonesian Muslim intellectuals who had shaped specific school of Islamic thought known as neo-modernism. One of contemporary issues that he was concerned with was the problem of religious plurality, which was a fact in Indonesian religious life and had been debated among Indonesian Muslim scholars before him. However, at his era, the discussion of such an issue became more controversial and attracted wider debate. This is because he interpreted “Islam,” which is commonly understood as religion of the followers of Prophet Muhammad, to mean “surrender” to God’s will which is at the heart of all prophetic religions before him. In addition, he extended the concept of people of the book (ahl al-kitab), which includes exclusively the adherents of Judaism and Christianity as traditionalists understand, to cover other religious traditions such as Hinduism, Buddhism, and so on. Drawing greatly on Nurcholish’s works, this article argues that his theology of religious pluralism can be categorized as inclusive, which is different from exclusivism.